ROBOT PELACAK MANUSIA MENGGUNAKAN WEBCAM SEBAGAI SENSOR VISUAL - Tjais, Randiansyah Ramadhan; Harianto, Harianto (Journal of Control and Network Systems, 2015)
Mobile robot is a type of robot that is able to move from one point to another. Mobile robot detects the surrounding objects and process it with the courtesy of webcam. With this particular superiority, mobile robot can facilitate humanâs work. One of the humanâs work that can be facilitated by mobile robot is any works within security field. Security tools used up until now is a surveillance camera, which has a downside of blind spots. Mobile robot is able to facilitate humanâs works with goals of strengthen the security by reducing blind spots.Along with the concerned mobile robot, the author would like to establish a robot that is capable to follow human while walking. The type of mobile robot used in this research is Robotino. The robot follows the human the time when the webcam detected human bodies. The robotâs webcam then, process the image received so that it can detect human bodies using image processing with Haar-like feature method. Then, the robot approaches the human body target that is already detected, using fuzzy logic to control the movement of robot.The human body tracking is capable to detect human body with the most effective detection range of 1-4 meters from the webcam of the robot. The robot is also able to perform tracking towards human bodies with the error rate of 9.6515875 %.